PKM Pendampingan Kelas Ibu Anti Razia (Kurang Gizi Dan Anemia) di Wilayah Kerja Puskesmas Durian Luncuk - Fatihatul Hayati; Safitri Safitri; Arnati Wulansari (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Stunting is still a national health problem, including in Jambi Province. The highest prevalence of stunted toddlers was found in Batanghari Regency, precisely in the Durian Luncuk Health Centre Working Area. Malnutrition and anemia in pregnant women will cause low birth weight and malnutrition in toddlers, including the stunting. The trend of the percentage of mothers giving birth to low birth weight babies (BBLR) in the last three years tends to increase, while babies with BBLR are more at risk of stunting. Efforts to prevent malnutrition and anemia in pregnant women include increasing the consumption of foods high in iron and protein around the mother's residence, which is the local wisdom of the region. The purpose of this activity is to carry out the assistance of anti-Razia (Malnutrition and Anemia) pregnant women's classes as a forum for health education for pregnant women and posyandu cadres to empower communities to prevent stunting, as well as midwives who can facilitate and become resource persons in anti-Razia women's classes with the method of theoretical exposure and demonstration of food processing practices which are divided into three classes where each class consists of three meetings. After a series of activities, the knowledge of pregnant women increased by 61%, the knowledge of posyandu cadres increased by 63%, and the knowledge of village midwives increased by 19%, the formation and implementation of the anti-Razia mother class, the implementation of cadre and village midwife training, increased knowledge and behavioral changes about the use of local food to prevent malnutrition and anemia in pregnant women and intellectual property rights for the Anti-Razia Mother Class module.